Austenitic stainless steel and hydrogen-resistant member

By optimizing the chemical composition and thermal processing technology of austenitic stainless steel, the problems of insufficient strength and excellent hydrogen embrittlement resistance in high-pressure hydrogen environments are solved, and the effects of high strength, excellent hydrogen embrittlement resistance and good processability are achieved.

CN119710442APending Publication Date: 2025-03-28DAIDO STEEL CO LTD

Patent Information

Application Number
CN202411358851.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-07-24
Filing Date
2024-09-27
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The existing austenitic stainless steels have problems such as insufficient strength and excellent hydrogen embrittlement resistance but increased size and weight in high-pressure hydrogen environments.

Method used

By optimizing the chemical composition of austenitic stainless steel, including controlling the content of elements such as C, Si, Mn, Ni, Cr, Mo, N, V, B, etc., and carrying out solid solution treatment and thermal processing, austenitic stainless steel with high tensile strength, excellent hydrogen embrittlement resistance and good processability were prepared.

Benefits of technology

The high strength and excellent hydrogen embrittlement resistance of austenitic stainless steel are achieved, while reducing the cost of materials and manufacturing costs, and maintaining high strength under solid solution treatment or welding conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119710442A_ABST
    Figure CN119710442A_ABST
Patent Text Reader

Abstract

The present invention relates to an austenitic stainless steel comprising: C < = 0.10 mass%, Si < = 0.50 mass%, 3.0 mass% < = Mn < = 8.0 mass%, P < = 0.30 mass%, S < = 0.30 mass%, 7.0 mass% < = Ni < = 12.0 mass%, 18.0 mass% < = Cr < = 28.0 mass%, 1.0 mass% < = Mo < = 3.0 mass%, 0.03 mass% < = V < = 0.50 mass%, 0.0003 mass% < = B < = 0.0300 mass%, 0.0001 mass% < = Ca < = 0.0300 mass%, 0.35 mass% < = N < = 0.80 mass%, 0.001 mass% < = Co < = 1.00 mass%, and optionally, W < = 2.0 mass%, Zr < = 0.20 mass%, Ta < = 0.50 mass%, and the balance being Fe. The remainder being Fe and unavoidable impurities, and the number density of the coarse alloy carbonitride is 3 * 105 / mm2 or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an austenitic stainless steel and a hydrogen-resistant component, and more particularly to an austenitic stainless steel having excellent strength and hydrogen embrittlement resistance, and a hydrogen-resistant component using the austenitic stainless steel. Background Art

[0002] In recent years, fuel cell vehicles that use hydrogen as fuel and hydrogen stations that supply hydrogen to fuel cell vehicles have been developed. Since various equipment used in fuel cell vehicles, hydrogen stations, etc. (hereinafter collectively referred to as "high-pressure hydrogen equipment") are used in a high-pressure hydrogen environment, the materials used in these equipment need to have excellent hydrogen embrittlement resistance. Stainless steel (especially austenitic stainless steel with increased nickel equivalent) has excellent hydrogen embrittlement resistance and is suitable for this type of application.

[0003] Among austenitic stainless steels, SUS316L is a material with excellent resistance to hydrogen embrittlement. Currently, according to the standards for compressed hydrogen containers for automobiles stipulated in the Japanese High-Pressure Gas Safety Law, SUS316L is approved as a stainless steel with excellent resistance to hydrogen embrittlement. However, since SUS316L has low strength, in the case where SUS316L is used for structural members of high-pressure hydrogen equipment, the structural members need to be designed to be thicker. Therefore, there is a problem that an increase in the size and weight of the equipment is inevitable. In order to reduce the weight of fuel cell vehicles, make hydrogen stations compact, and achieve high-pressure operation in hydrogen stations, it is preferred that the strength of the stainless steel used for these applications is high.

[0004] In order to solve this problem, various proposals have been made in the past.

[0005] For example, Patent Document 1 discloses stainless steel for high-pressure hydrogen, requiring:

[0006] (a) containing predetermined amounts of C, Si, Mn, Cr, Ni, V, N and Al, with the balance being Fe and impurities; and

[0007] (b) Satisfying 2.5Cr+3.4Mn<300N.

[0008] The same document describes:

[0009] (A) Solid solution strengthening with nitrogen is most effective in improving the strength of austenitic stainless steels, with strength increasing but ductility and toughness decreasing as the nitrogen content increases; and

[0010] (B) When the composition is adjusted to satisfy 2.5Cr+3.4Mn<300N, the tensile strength increases and the elongation also increases.

[0011] Patent Document 2 discloses an austenitic stainless steel for high-pressure hydrogen, requiring:

[0012] (a) containing a predetermined content of C, Si, Mn, Cr, Ni, Al, N, and at least one of V and Nb, with the balance being Fe and impurities;

[0013] (b) tensile strength of 800 MPa or more;

[0014] (c) having a grain size number greater than 8; and

[0015] (d) The content of alloy carbonitrides with a maximum diameter of 50nm to 1000nm is 0.4 pieces / µm 2 above.

[0016] The same document describes:

[0017] (A) When nitrogen is used as a solute element, the strength of the stainless steel can be improved, but the stacking fault energy is reduced, and therefore, the durability against hydrogen environment embrittlement is reduced;

[0018] (B) When V and / or Nb are added to steel, fine alloy carbides are precipitated during solution heat treatment and the grains are refined due to the pinning effect; and

[0019] (C) When the grain size is refined, the hydrogen environment embrittlement resistance of high nitrogen steel can be improved.

[0020] Patent Document 3 discloses an austenitic stainless steel, requiring:

[0021] (a) Containing predetermined contents of C, Si, Mn, P, S, Ni, Cr, Mo, N, Nb and V, with the balance being Fe and impurities;

[0022] (b) Satisfying 15≤12.6C+1.05Mn+Ni+15N;

[0023] (c) having a grain size number less than 8.0; and

[0024] (d) It has a tensile strength of 690 MPa or more.

[0025] The same document describes:

[0026] (A) When the grain size number is 8.0 or less, excellent machinability can be obtained;

[0027] (B) C, N, Mn, and Ni are all austenite stabilizing elements, and when the contents of these elements are optimized, austenite is stabilized and hydrogen embrittlement resistance is improved even when the grains are coarse; and

[0028] (C) When 1.0% or more of Mo is added, high tensile strength can be obtained even when the grain size number is less than 8.0.

[0029] In addition, Patent Document 4 discloses an austenitic stainless steel material, requiring:

[0030] (a) Containing predetermined contents of C, Si, Mn, P, S, Ni, Cr, N, Mo, V and Nb, with the balance being Fe and impurities;

[0031] (b) having a grain size number of 6.0 or more;

[0032] (c) tensile strength of 800 MPa or above;

[0033] (d) The difference between the maximum and minimum tensile strength is less than 50 MPa;

[0034] (e) The number of alloy carbonitrides with an equivalent circle diameter exceeding 1000 nm is 10 / mm 2 above; and

[0035] (f) The difference between the maximum and minimum values ​​of the grain size number is 1.5 or less.

[0036] The same document describes:

[0037] (A) when the grain size number is 6.0 or more and the difference between the maximum value and the minimum value of the grain size number (ΔGS) is 1.5 or less, the difference between the maximum value and the minimum value of the tensile strength is 50 MPa or less;

[0038] (B) when the difference between the initial temperature and the final temperature during hot working is 100°C or less, ΔGS can be controlled to be 1.5 or less; and

[0039] (C) When the grain size is 6.0 or more and the number of alloy carbonitrides exceeding 1000 nm is 10 / mm 2 When the tensile strength is 800 MPa or more, a tensile strength of 800 MPa or more can be obtained.

[0040] In the case where a material having excellent hydrogen embrittlement resistance is used as a structural member of a high-pressure hydrogen device, the material is generally subjected to processing such as cutting, cold working and welding. Therefore, this type of material is required not only to have excellent strength and hydrogen embrittlement resistance, but also to have excellent machinability such as machinability, cold working and weldability.

[0041] Furthermore, in order to reduce the manufacturing cost and maintenance cost of the high-pressure hydrogen equipment, it is preferred that the material used in the equipment can be used in a solution treated (solution heat treated) state or a welded state and the content of expensive elements such as Ni is small.

[0042] In this regard, the stainless steel for high-pressure hydrogen described in Patent Document 1 has a strength of 700 MPa or more after solution treatment. However, since the stainless steel described in this document has a large Mn content, excellent workability may not be obtained.

[0043] The austenitic stainless steel for high-pressure hydrogen described in Patent Document 2 achieves grain refinement and high strength by performing solution heat treatment, cold working, and secondary heat treatment. However, cold working and secondary heat treatment lead to increased manufacturing costs.

[0044] Furthermore, the austenitic stainless steel described in Patent Document 3 is premised on use in a hot-worked state. Therefore, the stainless steel described in the same document has an excessive amount of carbonitrides in the steel and has low workability.

[0045] Similarly, in Patent Document 4, a relatively large amount of relatively coarse alloy carbonitrides are precipitated by heat treatment at a low temperature (from 930° C. to less than 1000° C.) after hot working austenitic stainless steel. Therefore, the stainless steel described in Patent Document 4 is also considered to have low workability.

[0046] Reference List

[0047] Patent Literature

[0048] Patent Document 1: WO2004 / 083477A

[0049] Patent Document 2: WO2012 / 132992A

[0050] Patent Document 3: WO2015 / 159554A

[0051] Patent Document 4: WO2017 / 175739A Summary of the invention

[0052] The problem to be solved by the present invention is to provide an austenitic stainless steel having excellent hydrogen embrittlement resistance, high strength and excellent machinability.

[0053] Furthermore, another problem to be solved by the present invention is to provide a hydrogen-resistant component using such austenitic stainless steel.

[0054] The main points of the present invention for solving the above-mentioned problems are as follows.

[0055] [1] An austenitic stainless steel comprising:

[0056] C ≤ 0.10% by mass

[0057] Si ≤ 0.50% by mass

[0058] 3.0 mass% ≤ Mn ≤ 8.0 mass%,

[0059] P ≤ 0.30% by mass

[0060] S ≤ 0.30% by mass

[0061] 7.0 mass% ≤ Ni ≤ 12.0 mass%,

[0062] 18.0 mass% ≤ Cr ≤ 28.0 mass%,

[0063] 1.0 mass% ≤ Mo ≤ 3.0 mass%,

[0064] 0.03 mass% ≤ V ≤ 0.50 mass%,

[0065] 0.0003 mass% ≤ B ≤ 0.0300 mass%,

[0066] 0.0001 mass% ≤ Ca ≤ 0.0300 mass%,

[0067] 0.35 mass% ≤ N ≤ 0.80 mass%, and

[0068] 0.001 mass% ≤ Co ≤ 1.00 mass%,

[0069] Optionally,

[0070] W ≤ 2.0% by mass

[0071] Zr ≤ 0.20 mass%, and

[0072] Ta ≤ 0.50% by mass

[0073] The balance is Fe and unavoidable impurities, and

[0074] The number density of crude alloy carbonitrides is 3×10 5 Pieces / mm 2 the following.

[0075] Here, "coarse alloy carbonitride" refers to alloy carbonitride having an equivalent circle diameter greater than 1000 nm.

[0076] [2] The austenitic stainless steel according to [1], further satisfying at least one member selected from the following group:

[0077] 0.3 mass% ≤ W ≤ 2.0 mass%,

[0078] 0.01 mass% ≤ Zr ≤ 0.20 mass%, and

[0079] 0.10 mass% < Ta ≤ 0.50 mass%.

[0080] [3] The austenitic stainless steel according to [1] or [2], having a tensile strength of 690 MPa or more measured at 25°C.

[0081] [4] The austenitic stainless steel according to any one of [1] to [3], wherein the grain size number of the austenite grains is less than 8.0.

[0082] [5] The austenitic stainless steel according to any one of [1] to [4], wherein the austenitic stainless steel has a reduction of area measured at 25°C of 30% or more.

[0083] [6] A hydrogen-resistant component comprising the austenitic stainless steel according to any one of [1] to [5].

[0084] [7] The hydrogen resistant member according to [6], wherein the austenitic stainless steel includes a portion in a solution treated state.

[0085] [8] The hydrogen resistant member according to [6] or [7], comprising a butt welded portion, wherein

[0086] The welding tensile strength of the butt welded portion measured at 25°C is 690 MPa or more.

[0087] N is an austenite stabilizing element and a solid solution strengthening element, but is also an element that reduces stacking fault energy. On the other hand, for example, Si is an element that reduces grain boundary strength, and B is an element that improves grain boundary strength. Therefore, when a relatively large amount of N is added to steel and the composition is optimized at the same time (specifically, the content of elements that reduce grain boundary strength is limited, and an appropriate amount of elements that improve grain boundary strength are added), austenitic stainless steel having excellent hydrogen embrittlement resistance and high strength can be obtained. In addition, since the Ni content contained in the steel can be reduced, the cost of raw materials can be reduced.

[0088] In addition, the austenitic stainless steel according to the present invention exhibits high strength, for example, even in a solution treated state or a welded state. In addition, since the content of Mn is relatively small and the number density of coarse alloy carbides is also small, the austenitic stainless steel is excellent in machinability. In addition, when the manufacturing conditions are optimized, the grains are moderately coarsened, so the machinability is further improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0089] Figure 1 The relationship between Co content and relative area reduction at -60°C is shown in FIG. DETAILED DESCRIPTION

[0090] Hereinafter, embodiments of the present invention will be described in detail.

[0091] [1. Austenitic stainless steel]

[0092] [1.1. Main components]

[0093] The austenitic stainless steel according to the present invention contains the following elements, with the balance being Fe and inevitable impurities. The types of the added elements, the content ranges and the reasons for their limitations are as follows.

[0094] (1) C ≤ 0.10 mass%:

[0095] In the present invention, C is an impurity. When the C content is excessive, a large amount of carbides precipitate, resulting in deterioration of toughness, ductility and corrosion resistance. Therefore, the C content needs to be 0.10 mass % or less. The C content is preferably less than 0.05 mass %, more preferably 0.03 mass % or less.

[0096] In the present invention, the less the content of C, the better. However, an extreme reduction in the content of C leads to an increase in manufacturing cost. In consideration of manufacturing cost, the content of C is preferably 0.0005% by mass or more. The content of C is more preferably 0.001% by mass or more.

[0097] (2) Si ≤ 0.50 mass%:

[0098] In the present invention, Si is an impurity. Si combines with Ni and Cr to form intermetallic compounds. Si further promotes the growth of intermetallic compounds such as sigma phase. These intermetallic compounds reduce the hot working properties of steel. In addition, in the case of excessive Si content, the grain boundary strength is reduced and the hydrogen embrittlement resistance is reduced. Therefore, the Si content needs to be 0.50 mass% or less. The Si content is preferably 0.20 mass% or less, and more preferably 0.09 mass% or less.

[0099] In the present invention, the smaller the content of Si, the better. However, an extreme reduction in the content of Si leads to an increase in manufacturing costs. Considering the manufacturing cost, the content of Si is preferably 0.001 mass % or more. The content of Si is more preferably 0.01 mass % or more.

[0100] (3) 3.0 ≤ Mn ≤ 8.0 mass%:

[0101] Mn stabilizes austenite and prevents the formation of martensite, which has a high sensitivity to hydrogen embrittlement. In addition, Mn increases the solubility of N in the molten metal, thereby contributing to increased strength.

[0102] In order to achieve such an effect, the Mn content needs to be 3.0 mass % or more. The Mn content is preferably 5.1 mass % or more, and more preferably 5.5 mass % or more.

[0103] On the other hand, when the Mn content is excessive, the stacking fault energy and grain boundary strength are reduced, and the hydrogen embrittlement resistance is reduced. In addition, when the Mn content is excessive, the toughness, ductility and hot workability of the steel are also reduced. Therefore, the Mn content needs to be 8.0% by mass or less. The Mn content is preferably 6.9% by mass or less, more preferably 6.5% by mass or less.

[0104] (4) P ≤ 0.30 mass%:

[0105] In the present invention, P is an impurity. When the P content is excessive, the hot workability, toughness and ductility of the steel are reduced. In addition, when the P content is excessive, concerns about hardening cracks during welding are increased. Therefore, the P content needs to be 0.30% by mass or less. The P content is preferably less than 0.10% by mass, and more preferably 0.03% by mass or less.

[0106] In the present invention, the less the content of P, the better. However, an extreme reduction in the content of P leads to an increase in manufacturing costs. Considering the manufacturing cost, the content of P is preferably 0.0005% by mass or more. The content of P is more preferably 0.001% by mass or more.

[0107] (5) S ≤ 0.30 mass%:

[0108] In the present invention, S is an impurity. When the S content is excessive, the toughness and ductility of the steel and the hot workability are reduced. In addition, when the S content is excessive, the concern about cracks during welding is increased. Therefore, the S content needs to be 0.30% by mass or less. The S content is preferably less than 0.10% by mass, and more preferably 0.09% by mass or less.

[0109] In the present invention, the smaller the content of S, the better. However, an extreme reduction in the content of S leads to an increase in manufacturing costs. Considering the manufacturing cost, the content of S is preferably 0.0005% by mass or more. The content of S is more preferably 0.001% by mass or more.

[0110] (6) 7.0 ≤ Ni ≤ 12.0 mass%:

[0111] Ni stabilizes austenite and increases stacking fault energy, thereby improving hydrogen embrittlement resistance. To achieve this effect, the Ni content needs to be 7.0 mass % or more. The Ni content is preferably 9.0 mass % or more, and more preferably 9.5 mass % or more.

[0112] On the other hand, when the Ni content is excessive, the raw material cost increases. In addition, when the Ni content is excessive, the solubility of N in the molten metal decreases, thereby deteriorating the strength. Therefore, the Ni content needs to be 12.0% by mass or less. The Ni content is preferably 10.5% by mass or less, and more preferably 9.9% by mass or less.

[0113] (7) 18.0 ≤ Cr ≤ 28.0 mass%:

[0114] Cr improves the corrosion resistance of steel. In addition, Cr increases the solubility of N in the molten metal, which helps to improve the strength. In order to achieve this effect, the Cr content needs to be 18.0% by mass or more. The Cr content is preferably 20.0% by mass or more, and more preferably 22.0% by mass or more.

[0115] On the other hand, when the Cr content is excessive, intermetallic compounds or carbonitrides may precipitate excessively, and the toughness, ductility and corrosion resistance of the steel may be reduced. Therefore, the Cr content needs to be 28.0% by mass or less. The Cr content is preferably 26.0% by mass or less, and more preferably 25.0% by mass or less.

[0116] (8) 1.0 ≤ Mo ≤ 3.0 mass%:

[0117] Mo helps to improve strength by solid solution strengthening austenite or forming carbonitrides. In addition, Mo improves the corrosion resistance of steel. In order to achieve this effect, the content of Mo needs to be 1.0 mass % or more. The content of Mo is preferably 1.5 mass % or more, and more preferably 1.8 mass % or more.

[0118] On the other hand, when the Mo content is excessive, intermetallic compounds or carbonitrides may precipitate excessively, and the toughness and ductility of the steel may be reduced. In addition, when the Mo content is excessive, the cost of raw materials also increases. Therefore, the content of Mo needs to be 3.0% by mass or less. The content of Mo is preferably 2.5% by mass or less, and more preferably 2.2% by mass or less.

[0119] (9) 0.03 ≤ V ≤ 0.50 mass%:

[0120] V forms cemented carbide carbonitride to improve the strength of steel. To achieve this effect, the V content needs to be 0.03% by mass or more. The V content is preferably 0.05% by mass or more, and more preferably 0.08% by mass or more.

[0121] On the other hand, when the V content is excessive, alloy carbonitrides are excessively precipitated, and the toughness and ductility of the steel are reduced. Therefore, the V content needs to be 0.50 mass % or less. The V content is preferably 0.30 mass % or less, and more preferably 0.20 mass % or less.

[0122] (10) 0.0003 ≤ B ≤ 0.0300 mass%:

[0123] B segregates at the grain boundaries to increase the grain boundary fixing force, thereby improving the strength of the steel. In addition, B prevents the embrittlement of the steel in a hydrogen environment and improves the hydrogen embrittlement resistance. In addition, B improves the hot working properties of the steel. In order to achieve this effect, the content of B needs to be 0.0003% by mass or more. The content of B is preferably 0.0005% by mass or more, and more preferably 0.0010% by mass or more.

[0124] On the other hand, when the B content is excessive, when welding is performed without using a filler metal, the hardening cracking sensitivity of the molten metal increases. Therefore, the B content needs to be 0.0300 mass % or less. The B content is preferably 0.0100 mass % or less, and more preferably 0.0050 mass % or less.

[0125] (11) 0.0001 ≤ Ca ≤ 0.0300 mass%:

[0126] Ca improves the hot working properties of steel. To achieve this effect, the Ca content needs to be 0.0001 mass % or more. The Ca content is preferably 0.0003 mass % or more, and more preferably 0.0005 mass % or more.

[0127] On the other hand, when the Ca content is excessive, Ca and O combine to reduce the cleanliness of the steel. Therefore, hot workability is greatly reduced, and toughness and ductility are also reduced. Therefore, the Ca content needs to be 0.0300 mass % or less. The Ca content is preferably 0.0150 mass % or less, and more preferably 0.0100 mass % or less.

[0128] (12) 0.35 ≤ N ≤ 0.80 mass %:

[0129] N stabilizes austenite and improves hydrogen embrittlement resistance. In addition, N also improves the strength of steel through solid solution strengthening and the formation of nitrides. In addition, N improves the corrosion resistance of steel. In order to achieve this effect, the N content needs to be 0.35 mass% or more.

[0130] The N content is preferably 0.40 mass % or more, more preferably 0.46 mass % or more.

[0131] On the other hand, when the N content is excessive, coarse nitrides are generated, and the toughness and ductility of the steel are reduced. In addition, when the N content is excessive, the hot workability of the steel is reduced, or pores (defects) may be formed during welding. In addition, when N is excessive, the stacking fault energy is reduced, and the hydrogen embrittlement resistance is reduced. Therefore, the N content needs to be 0.80 mass% or less. The N content is preferably 0.60 mass% or less, and more preferably 0.53 mass% or less.

[0132] It should be noted that in high nitrogen steel, hydrogen embrittlement resistance may decrease due to deterioration of grain boundary strength, but in the present invention, since the grain boundary strength is improved by optimizing the Si content, B content, etc., deterioration of hydrogen embrittlement resistance can be prevented.

[0133] (13) 0.001 ≤ Co ≤ 1.00 mass%:

[0134] Examples of Co impacts include:

[0135] (a) Stabilizing the austenite structure to improve resistance to hydrogen embrittlement;

[0136] (b) The effect of increasing the stacking fault energy to improve the hydrogen embrittlement resistance;

[0137] (c) the effect of improving strength through solid solution strengthening;

[0138] (d) the effect of improving toughness; and

[0139] (e) Effect of suppressing the reduction of hydrogen embrittlement resistance after welding. To achieve this effect, the Co content needs to be 0.001 mass % or more. The Co content is preferably 0.07 mass % or more, more preferably 0.10 mass % or more, and further preferably 0.15 mass % or more.

[0140] On the other hand, an excessive Co content leads to an increase in cost. Therefore, the Co content is preferably 1.00 mass % or less.

[0141] [1.2. Sub-component elements]

[0142] In addition to the above-mentioned main constituent elements, the austenitic stainless steel according to the present invention may further contain one or two or more of the following elements. The types of the added elements, the content ranges and the reasons for their limitation are as follows.

[0143] (1) W ≤ 2.0 mass%:

[0144] W has the effect of improving corrosion resistance and the effect of improving strength by forming a solid solution or carbonitride. Therefore, the austenitic stainless steel according to the present invention may further contain W. In order to achieve such an effect, the content of W is preferably 0.3% by mass or more. The content of W is more preferably 0.8% by mass or more.

[0145] On the other hand, when the W content is excessive, the raw material cost increases. Therefore, the W content is preferably 2.0 mass % or less. The W content is more preferably 1.5 mass % or less.

[0146] (2) Zr ≤ 0.20 mass%:

[0147] Zr has the effect of forming a crystalline oxide. Since the crystallized oxide serves as a starting point for forming inclusions such as MnS and carbonitrides, the size of the inclusions can be reduced, and the toughness and ductility can be improved. Therefore, the austenitic stainless steel according to the present invention may further contain Zr instead of W or in addition to W. In order to achieve this effect, the content of Zr is preferably 0.01% by mass or more. The content of Zr is more preferably 0.05% by mass or more.

[0148] On the other hand, when the Zr content is excessive, rough oxides are formed, and toughness and ductility are reduced. Therefore, the Zr content is preferably 0.20 mass % or less. The Zr content is more preferably 0.15 mass % or less.

[0149] (3) Ta ≤ 0.50 mass%:

[0150] Ta has the effect of improving strength by forming a solid solution or carbonitride. Therefore, the austenitic stainless steel according to the present invention may further contain Ta. The austenitic stainless steel may contain only Ta, or may contain W and / or Zr in addition to Ta. In order to achieve this effect, the content of Ta is preferably greater than 0.10 mass %.

[0151] On the other hand, when the Ta content is excessive, the raw material cost increases. Therefore, the Ta content is preferably 0.50 mass % or less.

[0152] [1.3. Unavoidable impurities]

[0153] Inevitable impurities refer to elements mixed from ore or scrap used as steel raw materials, or from the environment of the manufacturing process, etc. Specific examples of inevitable impurities include the following elements in addition to the above-mentioned C, Si, P and S.

[0154] (1) Cu ≤ 0.5 mass%:

[0155] In the present invention, Cu is an impurity. When the Cu content is excessive, concerns about hardening cracks during welding increase. Therefore, the Cu content is preferably 0.5% by mass or less. The Cu content is more preferably 0.4% by mass or less.

[0156] In the present invention, the smaller the content of Cu, the better. However, an extreme reduction in the content of Cu will lead to an increase in manufacturing costs. Considering the manufacturing cost, the content of Cu is preferably 0.005 mass % or more. The content of Cu is more preferably 0.010 mass % or more.

[0157] (2) Al ≤ 0.10 mass%:

[0158] In the present invention, Al is an impurity. Similar to Si, Al has the effect of deoxidizing steel. However, in the case of excessive Al content, excessive nitrides are formed, and the toughness and ductility of the steel are reduced.

[0159] In addition, when the Al content is too high, the penetration depth during welding becomes shallow. Therefore, the Al content is preferably 0.10 mass % or less. The Al content is more preferably 0.05 mass % or less.

[0160] In the present invention, the less Al content, the better. However, an extreme reduction in Al content leads to an increase in manufacturing cost. Considering the manufacturing cost, the Al content is preferably 0.0005 mass % or more. The Al content is more preferably 0.001 mass % or more.

[0161] (3) O ≤ 0.050 mass%:

[0162] In the present invention, O is an impurity. O reduces the hot workability of the base material during the manufacturing process. In addition, O reduces the cleanliness of the steel and reduces the toughness and ductility of the steel. Therefore, the content of O is preferably 0.050 mass % or less. The content of O is more preferably 0.030 mass % or less, and even more preferably 0.010 mass % or less.

[0163] In the present invention, the smaller the content of O, the better. However, an extreme reduction in the content of O leads to an increase in manufacturing cost. In consideration of manufacturing cost, the content of O is preferably 0.0005% by mass or more. The content of O is more preferably 0.001% by mass or more, and even more preferably 0.002% by mass or more.

[0164] (4) Other impurities:

[0165] In addition to the above-mentioned components, the austenitic stainless steel according to the present invention may further contain the following components in the following contents. In this case, these components are regarded as unavoidable impurities in the present invention.

[0166] Nb < 0.05 mass%, Ta ≤ 0.10 mass%, Ti ≤ 0.10 mass%, Sn ≤ 0.03 mass%, Zn ≤ 0.03 mass%, Pd ≤ 0.03 mass%, Cd ≤ 0.03 mass%, Ag ≤ 0.03 mass%, Ga ≤ 0.03 mass%, As≤ 0.03 mass%, La ≤ 0.03 mass%, Ce ≤ 0.03 mass%, Y ≤ 0.03 mass%, Sm ≤ 0.03 mass%, Se ≤ 0.03 mass%, Te ≤ 0.03 mass%, Bi ≤ 0.03 mass%, Pb ≤ 0.03 mass%, Mg ≤ 0.03 mass%, Sb ≤ 0.03 mass%, REM ≤ 0.03 mass%.

[0167] [1.4. Characteristics]

[0168] [1.4.1. Number density of crude alloy carbonitrides]

[0169] “Coarse alloy carbonitride” refers to alloy carbonitride having an equivalent circle diameter greater than 1000 nm.

[0170] "Alloy carbonitride" refers to a material containing C or N or both in precipitates and inclusions containing carbonitride-forming elements such as Cr, V, Mo, W, Ta, Nb, or Ti as main components. Examples of alloy carbonitrides include:

[0171] (a) Cr2N

[0172] (b) Z phase (i.e., Cr(Nb,V)(C,N)); and

[0173] (c) MX type carbonitrides (M: Cr, V, Mo, Ta, Nb, Ti, etc., X: C, N).

[0174] The “number density of crude alloy carbonitrides” refers to the number of crude alloy carbonitrides per unit area (pieces / mm 2 ). Specifically, the number density is determined by the following method.

[0175] That is, a sample of the austenitic stainless steel material is taken so as to include the central part of the cross section perpendicular to the rolling or forging extension direction. The above-mentioned observation area of ​​the sample is mirror-polished. Thereafter, arbitrary 10 fields of view (200 μm × 200 μm, 200 μm) in the observation area are observed by using a scanning electron microscope (SEM) equipped with an energy dispersive X-ray spectrometer (EDS) to identify alloy carbonitrides from precipitates and inclusions in each field of view.

[0176] The equivalent circle diameter of the alloy carbonitride identified in each field of view is obtained by image analysis. The equivalent circle diameter refers to the diameter (nm) when the area of ​​the alloy carbonitride in the field of view is converted into a circle. The number of alloy carbonitrides (crude alloy carbonitrides) each having an equivalent circle diameter greater than 1000nm is calculated. In the present invention, the average number of crude alloy carbonitrides obtained in 10 fields of view is defined as the "number density of crude alloy carbonitrides (numbers / mm 2 )".

[0177] In the case where the crude alloy carbonitrides are excessively precipitated in the matrix phase, the machinability (cutting property) deteriorates due to tool wear caused by the crude alloy carbonitrides. On the other hand, when the composition of the austenitic stainless steel is optimized and hot working and / or solution treatment is performed under appropriate conditions, the number density of the crude alloy carbonitrides can be reduced. In order to obtain excellent machinability, the number density of the crude alloy carbonitrides is preferably 3×10 5 Pieces / mm 2 The number density is more preferably 1×10 4 Pieces / mm 2 less than 1×10 3 Pieces / mm 2 the following.

[0178] On the other hand, since even coarse alloy carbonitrides contribute to tensile strength, in the case of desiring to obtain austenitic stainless steel having higher strength, the number density is preferably 1 piece / mm 2 More than 10 / mm 2 above.

[0179] [1.4.2. Tensile strength]

[0180] The “tensile strength” refers to the tensile strength obtained by conducting a tensile test using a No. 14A test piece having a parallel portion diameter of 6 mm in accordance with JIS Z2241 (2011).

[0181] By optimizing hot working conditions and / or solution treatment conditions, the austenitic stainless steel according to the present invention achieves a tensile strength of 690 MPa or more measured at 25° C. When the composition is further optimized, the tensile strength may be 750 MPa or more, or 800 MPa or more.

[0182] [1.4.3. Grain size number]

[0183] The “grain size number” refers to a value measured according to JIS G0551 (2005). Specifically, the grain size number is determined by the following method.

[0184] That is, the specimen for microscopic observation is taken from austenitic stainless steel. The microscopic measurement method of the grain size specified in JIS G0551 (2005) is performed by evaluating the grain size number using the taken test piece.

[0185] More specifically, the surface of the test piece is etched using a well-known etchant (glycerol, Kalling reagent, or Marbles reagent, etc.) to reveal the grain boundaries on the surface. In 10 fields of view of the etched surface, the number of grain sizes in each field of view is obtained. The area of ​​each field of view is about 40 mm 2 .

[0186] The grain size number of each viewing field is evaluated by comparison with the grain size reference chart defined in Section 7.1.2 of JIS G0551 (2005). The average grain size number of the viewing field is defined as the grain size number of the austenitic stainless steel according to the present invention.

[0187] In the austenitic stainless steel according to the present invention, since the composition is optimized, the grain size number of the austenite grains can be less than 8.0 by optimizing the hot working conditions and / or the solution treatment conditions. In the case where the grain size number is less than 8.0, the grain size is moderately increased and the cutting resistance is reduced. In addition, the chips can be easily separated from the processed material and the cutting tool during the cutting process, and the processability of the chips is improved. That is, in the case where the grain size number is less than 8.0, the processability of the steel is improved. The grain size number is preferably 7.0 or less.

[0188] On the other hand, in the case where the grain size number is too small, the grain size increases excessively, which may reduce the tensile strength of the steel. Therefore, the grain size number is preferably 2.0 or more. The grain size number is more preferably 3.0 or more.

[0189] [1.4.4. Sectional reduction]

[0190] “Reduction of area” refers to the difference between the original cross-sectional area (S0) of the tensile specimen before the test and the cross-sectional area (S0) of the tensile specimen after the test when a tensile test is conducted in accordance with JIS Z2241 (2011) using a No. 14A test piece with a parallel portion diameter of 6 mm. u ) relative to the original cross-sectional area (S0) (= (S0-S u )×100 / S0).

[0191] By optimizing hot working conditions and / or solution treatment conditions, the austenitic stainless steel according to the present invention can have a cross-sectional reduction of 30% or more measured at 25° C. When the composition is further optimized, the cross-sectional reduction can be 40% or more, or 50% or more.

[0192] Here, in the present invention, "solution treatment" refers to a process of heating a steel material at 800°C to 1200°C for 1 minute or more and cooling the steel material at a cooling rate of water cooling, oil cooling or air cooling or an equivalent cooling rate thereof.

[0193] [1.4.5. Hydrogen embrittlement resistance]

[0194] The quality of hydrogen embrittlement resistance can be evaluated based on the size of the relative reduction of area.

[0195] Here, the "relative reduction of area" refers to a value represented by the following equation (1). The larger the value of the relative reduction of area represented by equation (1), the better the hydrogen embrittlement resistance.

[0196] Relative area reduction = A / B (1)

[0197] here,

[0198] A is the reduction of area of ​​the round bar tensile test piece when the low strain rate test is carried out under the conditions of room temperature test temperature and 87.5 MPa hydrogen test atmosphere, and

[0199] B is the cross-sectional reduction of the round bar tensile test piece when the low strain rate test is carried out under the conditions of room temperature test temperature and 87.5 MPa helium test atmosphere.

[0200] It should be noted that in each measurement of A and B, a round bar tensile specimen with a parallel section diameter of 4 mm was used and the strain rate was 7 × 10 -5 / s.

[0201] Furthermore, it is known that the relative reduction of area, which is an indicator of hydrogen embrittlement resistance, is inferior in a low strain rate test at low temperature than in a low strain rate test at room temperature. The austenitic stainless steel according to the present invention exhibits excellent relative reduction of area even in a low strain rate test at low temperature.

[0202] In the low strain rate test at low temperature, the relative reduction of area is a value expressed by the following formula (2). The larger the relative reduction of area expressed by the formula (2), the better the hydrogen embrittlement resistance.

[0203] Relative area reduction = C / D (2)

[0204] C is the reduction of area of ​​the round bar tensile test piece when tested at a low strain rate at a test temperature of -60°C and a hydrogen test atmosphere of 87.5 MPa, and

[0205] D is the reduction of area of ​​the round bar tensile test piece when the low strain rate test is carried out at a test temperature of -60°C and a helium test atmosphere of 87.5MPa.

[0206] It should be noted that in each measurement of C and D of the material before welding, a round bar tensile test piece with a parallel portion diameter of 4 mm was used. On the other hand, in each measurement of C and D of the material after welding, a plate-shaped tensile test piece (width of the parallel portion: 5 mm, thickness of the parallel portion: 1.5 mm) was used. Regardless of the shape of the test piece and the test temperature, the strain rate was 7 × 10 -5 / s.

[0207] The austenitic stainless steel according to the present invention has excellent hydrogen embrittlement resistance because its composition is optimized. In the austenitic stainless steel according to the present invention, when the composition and structure are optimized, the relative reduction in area can be 0.8 or more. When the components and / or structure are further optimized, the relative reduction in area can be 0.9 or more.

[0208] [1.5. Application]

[0209] Since the austenitic stainless steel according to the present invention has excellent hydrogen embrittlement resistance, the austenitic stainless steel can be used for:

[0210] (a) as austenitic stainless steel for use with high pressure hydrogen; or

[0211] (b) As austenitic stainless steel for use in liquid hydrogen environments.

[0212] In particular, since the austenitic stainless steel according to the present invention has excellent toughness at extremely low temperatures in addition to hydrogen embrittlement resistance, the austenitic stainless steel can be used as, for example, the following materials:

[0213] (a) components for liquid hydrogen pump-pressurized hydrogen stations, and

[0214] (b) Components used in liquid hydrogen environments, such as liquid hydrogen valves and pump components.

[0215] [2. Method for producing austenitic stainless steel]

[0216] The austenitic stainless steel according to the present invention can be obtained by the following method

[0217] (a) melting and casting mixed raw materials to obtain a predetermined composition to prepare an ingot,

[0218] (b) subjecting the obtained ingot to initial hot working,

[0219] (c) subjecting the material obtained by the primary hot working to a secondary hot working,

[0220] (c) if necessary, cold working of the material after secondary hot working,

[0221] (d) if necessary, solution treating the material after secondary hot working or after cold working, and

[0222] (e) If necessary, post-process the material after secondary hot working, cold working or solution treatment.

[0223] [2.1. Melting and casting process]

[0224] First, raw materials mixed to have a predetermined composition are melted and cast. The method and conditions of melting and casting are not particularly limited, and the best method and conditions can be selected according to the purpose. For example, an electric furnace, an argon oxygen decarburization (AOD) furnace, a vacuum oxygen decarburization (VOD) furnace, etc. can be used to manufacture molten steel.

[0225] It should be noted that, if necessary, the obtained ingot may be subjected to a homogenization heat treatment to eliminate segregation.

[0226] [2.2. Primary thermal processing]

[0227] Next, the obtained ingot is subjected to primary hot working. The primary hot working is performed to break the rough cast structure and refine the structure while transforming the ingot into a steel material such as a slab, bloom, and billet. The primary hot working method is not particularly limited, and the best method can be selected according to the purpose. Examples of the primary hot working method include hot forging and hot rolling.

[0228] It should be noted that steel materials such as slabs, blooms and billets can be directly manufactured from manufactured molten steel by a continuous casting method. In this case, the primary hot working process can be omitted.

[0229] [2.3. Secondary thermal processing]

[0230] Next, the material obtained in the primary hot working process is subjected to secondary hot working. The secondary hot working is performed to finish the material obtained in the primary hot working process into a final product shape (e.g., steel plate, steel bar, wire rod, and steel pipe) or a shape close thereto. The secondary hot working method is not particularly limited, and the best method can be selected according to the purpose. Examples of the secondary hot working method include hot rolling, hot extrusion, and hot piercing rolling.

[0231] The conditions of the secondary hot working are not particularly limited, and the optimal conditions can be selected according to the purpose. In addition, the secondary hot working can be performed multiple times according to the purpose. In the case where the heating temperature of the steel material before the secondary hot working is too low, the grains may be excessively refined and the machinability may be reduced. Therefore, the heating temperature is preferably 900°C or more.

[0232] On the other hand, if the heating temperature is too high, there is a concern that local melting may occur. Therefore, the heating temperature is preferably 1300° C. or lower.

[0233] In the case where secondary hot working is performed multiple times, the grain and number density of the coarse alloy carbonitride can be optimized by optimizing the temperature of the steel material when the final secondary hot working is completed. In the case where the temperature of the steel material is too low, the grains may be excessively refined and the cuttability may be reduced. Therefore, the temperature of the steel material is preferably 800°C or more.

[0234] On the other hand, if the temperature of the steel material is too high, there is a concern that local melting may occur. Therefore, the temperature of the steel material is preferably 1200° C. or lower.

[0235] [2.4. Cold working process]

[0236] Next, if necessary, the material may be cold worked after the secondary hot working. The cold working method is not particularly limited, and the best method may be selected according to the purpose. For example, in the case of cold working the material into a steel pipe, a cold drawing method is preferably used. Alternatively, in the case of processing the material into a steel plate, a cold rolling method is preferably used.

[0237] [2.5. Solution treatment process]

[0238] Next, if necessary, the material subjected to secondary hot working or the material subjected to cold working may be subjected to solution treatment. The solution treatment may be performed only once, or may be performed a plurality of times.

[0239] The solution treatment temperature affects the properties of the material. In the case where the solution treatment is not performed, or in the case where the solution treatment temperature is too low, the number density of the coarse alloy carbonitride may be excessively increased, and the cross-sectional reduction rate may be reduced. In addition, the grains may be excessively refined, and the cuttability may be reduced. Therefore, the solution treatment temperature is preferably 800°C or more. The solution treatment temperature is more preferably 1000°C or more.

[0240] On the other hand, if the solution treatment temperature is too high, there is a concern that local melting may occur. Therefore, the solution treatment temperature is preferably 1200° C. or lower.

[0241] The optimum holding time at the solution treatment temperature can be selected according to the purpose. Generally, the longer the holding time at the solution treatment temperature, the smaller the number density of the coarse alloy carbonitrides.

[0242] On the other hand, in the case where the holding time is longer than necessary, the grains are excessively coarsened. The optimum holding time varies depending on the solution treatment temperature, but is generally 1 minute to 3 hours. After the holding time is over, the material is cooled by water cooling, oil cooling or air cooling or at their equivalent cooling rates.

[0243] [2.6. Post-processing process]

[0244] If necessary, the material subjected to secondary hot working, the material subjected to cold working or the material subjected to solution treatment can be further post-processed. Examples of post-processing include cutting processing, welding and cold working. The components thus obtained are used in various applications.

[0245] [3. Hydrogen resistant components]

[0246] The hydrogen resistant component according to the present invention includes the austenitic stainless steel according to the present invention.

[0247] [3.1. Materials]

[0248] The austenitic stainless steel according to the present invention has excellent hydrogen embrittlement resistance because the austenitic stainless steel has a predetermined composition. Since other aspects regarding the composition of the austenitic stainless steel are as described above, description is omitted.

[0249] The austenitic stainless steel constituting the hydrogen resistant member may be in a hot working state, a cold working state, a solution treatment state, or a state after necessary post-treatment after the solution treatment. In order to reduce the number density of crude alloy carbonitrides and reduce manufacturing costs, the austenitic stainless steel constituting the hydrogen resistant member preferably includes a portion in a solution treatment state.

[0250] Here, "including the portion in the solution treated state" means

[0251] Case (a) The entire austenitic stainless steel constituting the hydrogen resistant component is in the solution treated state, or

[0252] Case (b) A part of the austenitic stainless steel constituting the hydrogen resistant member has been subjected to necessary post-treatment (e.g., cutting treatment and welding), while the other part thereof remains in the solution treated state.

[0253] [3.2. Shape]

[0254] The shape of the hydrogen resistant member is not particularly limited, and an optimal shape can be selected according to the purpose. Examples of the shape of the hydrogen resistant member include a tube, a rod, a wire, and a plate.

[0255] In addition, the hydrogen resistant member may be a member including a welded portion obtained by welding members each having a predetermined shape. The type of the joint (i.e., welded joint) of the welded portion is not particularly limited, and the optimal welded joint may be selected according to the purpose. Examples of welded joints include butt joints, T-joints, corner joints, lap joints, and edge joints.

[0256] In the case where the hydrogen resistant member includes a welded portion, the welding method is not particularly limited, and the best method can be selected according to the purpose. The welding method may be a welding method using a filler metal, or a welding method not using a filler metal. Examples of the filler metal include YS316L, YS309LMo, YS308L, YS308H, YS308N2, and YS308LN.

[0257] Examples of the welding method using the filler metal include a TIG welding method, a plasma welding method, a laser welding method, a MIG welding method, a MAG welding method, and a shielded metal arc welding method.

[0258] Examples of the welding method that does not use a filler metal include a TIG welding method, a plasma welding method, and a laser welding method.

[0259] [3.3. Tensile strength of welded parts]

[0260] In the case where the hydrogen resistant member includes a welded portion, it is preferred that the member is subjected to solution treatment before welding and has a tensile strength of 690 MPa or more measured at 25° C. The tensile strength measured at 25° C. is more preferably 750 MPa or more, and even more preferably 800 MPa or more. In the case of welding by using a high-strength member, a high-strength hydrogen resistant member can be obtained.

[0261] Furthermore, when the composition and structure of austenitic stainless steel are optimized, and the welding method and welding conditions are optimized, a hydrogen-resistant component having high strength even in the welded state can be obtained.

[0262] For example, when the heat input is 0.20 kJ / mm to 0.60 kJ / mm, by using a TIG welding method with or without a filler metal for butt welding, a hydrogen-resistant component including a butt weld portion can be obtained. At this time, when the composition and structure of the austenitic stainless steel are optimized, a hydrogen-resistant component including a butt weld portion and having a tensile strength of 690 MPa or more of the butt weld portion measured at 25°C can be obtained. When the composition and structure of the austenitic stainless steel are further optimized, the tensile strength of the weld portion during welding measured at 25°C may be 750 MPa or more, or 800 MPa or more.

[0263] Here, the “tensile strength of the butt welded portion” refers to the tensile strength when a tensile test is performed using a No. 1A test piece with a parallel portion width of 12 mm and a plate thickness of 1.5 mm in accordance with JIS Z3121 (2013).

[0264] [4. Function]

[0265] N is an austenite stabilizing element and a solid solution strengthening element, but is also an element that reduces stacking fault energy. On the other hand, for example, Si is an element that reduces grain boundary strength, and B is an element that improves grain boundary strength. Therefore, when a relatively large amount of N is added to steel and the composition is optimized at the same time (specifically, the content of elements that reduce grain boundary strength is limited, and an appropriate amount of elements that improve grain boundary strength are added), austenitic stainless steel having excellent hydrogen embrittlement resistance and high strength can be obtained. In addition, since the Ni content contained in the steel can be reduced, the cost of raw materials can be reduced.

[0266] In addition, the austenitic stainless steel according to the present invention exhibits high strength, for example, even in a solution treated state or a welded state. In addition, since the content of Mn is relatively small and the number density of coarse alloy carbides is also small, the austenitic stainless steel is excellent in machinability. In addition, when the manufacturing conditions are optimized, the grains are moderately coarsened, so the machinability is further improved.

[0267] [Example]

[0268] (Examples 1 to 10, Comparative Examples 1 to 9)

[0269] [1. Sample preparation]

[0270] In a vacuum induction furnace, 50 kg of steel having the composition shown in Table 1 was melted and cast into an ingot. Then, the ingot was hot forged, hot rolled, solution treated, and machined to produce a steel rod with a diameter of 30 mm. In Table 1, the steels in Examples 5 to 7 have the same composition as the steel in Example 4, and the steel in Comparative Example 8 has the same composition as the steel in Comparative Example 7. It should be noted that in Example 7 and Comparative Example 7, solution treatment was not performed. In addition, in Comparative Example 8, the solution treatment temperature was 700°C. Except for Example 7 and Comparative Examples 7 and 8, the solution treatment temperature was 900°C to 1100°C.

[0271] Furthermore, two steel plates were separately prepared and butt-welded without filler metal at a heat input of 0.20 kJ / mm to 0.60 kJ / mm by a TIG welding method.

[0272] [Table 1]

[0273]

[0274] [Table 1 (continued)]

[0275]

[0276] [2. Test method]

[0277] [2.1. Grain size measurement]

[0278] Each steel bar was cut parallel to the rolling direction. A sample for grain size measurement was taken out, using the surface close to the central axis of the steel bar among the cut surfaces as the observation surface. Well-known electropolishing was performed on the observation surface of each sample. The grain size number of the observation surface after electropolishing was determined based on the above method.

[0279] [2.2. Measurement of the number density of carbonitrides in crude alloys]

[0280] The number density of the crude alloy carbonitrides was measured by the method described above.

[0281] [2.3. Reduction of fracture area and evaluation of tensile strength]

[0282] A round bar tensile test piece was taken out from the center part of each steel bar. The parallel part of the round bar tensile test piece is parallel to the rolling direction of the steel bar. The diameter of the parallel part is 6 mm. The tensile strength TS (MPa) was obtained by performing a tensile test on the round bar tensile test piece in the atmosphere at normal temperature (25°C).

[0283] In addition, a tensile test was also performed on each butt-welded member. Specifically, a plate-shaped tensile test piece having a welded portion at the center of the parallel portion was prepared from the butt-welded member. The width of the parallel portion was 12 mm, and the thickness of the parallel portion was 1.5 mm. The tensile strength TS (MPa) of the butt-welded portion was obtained by performing a tensile test on the plate-shaped tensile test piece at normal temperature.

[0284] In the tensile test using a round bar tensile test piece or a plate tensile test piece, the case where the measured tensile strength TS (MPa) is 690 MPa or more (which is the strength required for the base material) is judged as "A (high strength)", and the case where the measured tensile strength TS (MPa) is less than 690 MPa is judged as "B".

[0285] In addition, the area reduction ratio is calculated based on the area of ​​the fracture surface of the round bar tensile test piece after the tensile test. The case where the area reduction ratio is 30% or more is judged as "A (high area reduction ratio)", and the case where the area reduction ratio is less than 30% is judged as "B".

[0286] [2.4. Hydrogen embrittlement resistance evaluation]

[0287] [2.4.1. No welding]

[0288] Low strain rate tests were performed to evaluate hydrogen compatibility. The test temperature was room temperature or -60°C, and the test atmosphere was 87.5 MPa of helium or hydrogen. A round bar tensile test piece with a parallel section diameter of 4 mm was used as the test piece. The strain rate was 7×10 -5 / s.

[0289] Based on the fracture surface area of ​​the round bar tensile test piece after the low strain rate test, the cross-sectional reduction ratio in hydrogen and the cross-sectional reduction ratio in helium were calculated respectively. In addition, based on these cross-sectional reduction ratios at the time of rupture, the relative cross-sectional reduction ratio at room temperature (=A / B) and the relative cross-sectional reduction ratio at -60°C (=C / D) were calculated. In any case, the cross-sectional reduction ratio of 0.9 or more was judged as "S (particularly excellent hydrogen embrittlement resistance)", the cross-sectional reduction ratio of 0.8 or more and less than 0.9 was judged as "A (excellent hydrogen embrittlement resistance)", and the cross-sectional reduction ratio of less than 0.8 was judged as "B".

[0290] It should be noted that the reduction in area of ​​austenitic stainless steel is most significant in a high pressure hydrogen environment at -60°C.

[0291] [2.4.2. Welding]

[0292] The low strain rate test at -60°C and the measurement of the reduction of area (=C / D) at -60°C were performed in the same manner as in "2.4.1 Without welding", except that a plate-shaped tensile test piece having a welded portion at the center of the parallel portion (width of the parallel portion: 5 mm, thickness of the parallel portion: 1.5 mm) was used as the test piece.

[0293] [2.5. Relative wear evaluation]

[0294] A rod-shaped test piece was taken out from the center portion of each steel bar. The parallel portion of the rod-shaped test piece was parallel to the rolling direction of the steel bar. The rod-shaped test piece had a circular cross section with a diameter of 8 mm.

[0295] The peeling treatment was performed on the bar-shaped test piece for 5 minutes. A cemented carbide tool without coating treatment corresponding to P20 in the JIS standard was used as a tool for the peeling treatment.

[0296] The cutting speed was 100 m / min, the feed speed was 0.2 mm / rev, and the cut was 1.0 mm. No lubricating oil was used during the stripping process. The stripping process was carried out under the above conditions, and the flank wear amount W1 (mm) of the cemented carbide tool after the test was measured.

[0297] In addition, a rod-shaped test piece (hereinafter referred to as a "reference test piece") having a chemical composition corresponding to that of SUS316 in the JIS standard was prepared. The shape of the reference test piece was the same as that of the rod-shaped test piece. The peeling treatment was performed under the same conditions as above by using the reference test piece, and the rear flank wear amount W0 (mm) of the cemented carbide tool after the test was measured.

[0298] Based on the measurement results, the relative wear amount ratio defined by the following equation (3) was obtained: The case where the relative wear amount ratio was 0.40 or more was judged as "A (excellent in cutting performance)", and the case where the relative wear amount ratio was less than 0.40 was judged as "B".

[0299] Relative wear ratio = W0 / W1 (3)

[0300] [3. Results]

[0301] The results are shown in Table 2. Figure 1 The relationship between Co content and relative reduction of area (RRA) at -60°C is shown in Table 2 and Figure 1 The following can be found in .

[0302] (1) The tensile strength was low in Comparative Examples 1 and 2. This is considered to be because the N content was small.

[0303] (2) In Comparative Example 3, the hydrogen embrittlement resistance is low. This is considered to be because the Si content is too high.

[0304] (3) In Comparative Example 4, the hydrogen embrittlement resistance is low. This is considered to be because the B content is small.

[0305] (4) In Comparative Example 5, the number density of crude alloy carbonitrides was high and the machinability was poor. This is considered to be because excessive Nb increased the number density of crude alloy carbonitrides and excessively promoted grain refinement, and because abrasive wear of the tool was promoted by the crude alloy carbonitrides.

[0306] (5) In Comparative Example 6, the number density of crude alloy carbonitrides was high and the machinability was poor. This is considered to be because excessive Ti contained increased the number density of crude alloy carbonitrides and excessively promoted grain refinement, and because abrasive wear of the tool was promoted by the crude alloy carbonitrides.

[0307] (6) In Comparative Example 7, the number density of the coarse alloy carbonitrides was high and the number of grain sizes was large. Therefore, it is considered that the machinability was poor. This is considered to be because the temperature at which the final secondary hot working was completed was low.

[0308] (8) In Comparative Example 8, the number density of the coarse alloy carbonitrides was high and the grain size was large. Therefore, it was considered that the machinability was poor. This was considered to be because the solution treatment temperature was low.

[0309] (9) In each of Examples 1 to 10, the grain size number is less than 8, and the hydrogen embrittlement resistance is excellent. In addition, the tensile strength is 690 MPa or more, and the area reduction is also 30% or more. In addition, in all Examples 1 to 10, the relative wear amount ratio is 0.40 or more.

[0310] (10) The number density of crude alloy carbonitrides of Examples 1 to 4 is smaller than that of Examples 5 to 7. This is considered to be because the hot working conditions and / or the solution treatment conditions are further optimized.

[0311] (11) In Example 8, since W is contained, the tensile strength is improved compared with Examples 1 to 7.

[0312] (12) In Example 9, since Zr is contained, the reduction of area is improved compared with Examples 1 to 7. This is considered to be because inclusions such as MnS are minute.

[0313] (13) In Example 10, since Ta is contained, the tensile strength is improved compared with Examples 1 to 7.

[0314] (14) In the case of no welding, the relative reduction of area (RRA) at -60°C exceeds 0.9 even when the Co content is less than 0.001 mass%. On the other hand, in the case of welding, when the Co content is less than 0.001 mass%, the relative reduction of area (RRA) at -60°C is less than 0.8. See Comparative Example 9.

[0315] (15) In the case of no welding, the relative reduction of area (RRA) at -60°C gradually increases with the increase of Co content. On the other hand, in the case of welding, the relative reduction of area (RRA) at -60°C increases rapidly with the increase of Co content. In particular, when the Co content is 0.15 mass% or more, the relative reduction of area (RRA) at -60°C in the case of welding is equivalent to the relative reduction of area in the case of no welding. See Figure 1 .

[0316] [Table 2]

[0317]

[0318] [Table 2 (continued)]

[0319]

[0320] Although the embodiments of the present invention have been described in detail above, the present invention is not limited to the above embodiments, and various modifications may be made thereto without departing from the subject matter of the present invention. This application is based on Japanese Patent Application No. 2023-165246 filed on September 27, 2023 and Japanese Patent Application No. 2024-118404 filed on July 24, 2024, the contents of which are incorporated herein by reference.

[0321] Industrial Applicability

[0322] The austenitic stainless steel according to the present invention can be used as a structural member used in a high-pressure hydrogen device.

Claims

1. An austenitic stainless steel comprising: C ≤ 0.10 mass%, Si ≤ 0.50 mass%, 3.0 mass% ≤ Mn ≤ 8.0 mass%, P ≤ 0.30 mass%, S ≤ 0.30 mass%, 7.0 mass% ≤ Ni ≤ 12.0 mass%, 18.0 mass% ≤ Cr ≤ 28.0 mass%, 1.0 mass% ≤ Mo ≤ 3.0 mass%, 0.03 mass% ≤ V ≤ 0.50 mass%, 0.0003 mass% ≤ B ≤ 0.0300 mass%, 0.0001 mass% ≤ Ca ≤ 0.0300 mass%, 0.35 mass% ≤ N ≤ 0.80 mass%, and 0.001 mass% ≤ Co ≤ 1.00 mass%, and Optionally, W ≤ 2.0% by mass Zr ≤ 0.20 mass%, and Ta ≤ 0.50% by mass The balance is Fe and unavoidable impurities, and The number density of crude alloy carbonitrides is 3×10 5 Pieces / mm 2 Hereinafter, "coarse alloy carbonitride" refers to alloy carbonitride having an equivalent circle diameter greater than 1000 nm.

2. The austenitic stainless steel according to claim 1, further satisfying at least one selected from the group consisting of: 0.3 mass % ≤ W ≤ 2.0 mass %, 0.01 mass % ≤ Zr ≤ 0.20 mass %, and 0.10 mass % < Ta ≤ 0.50 mass %.

3. The austenitic stainless steel according to claim 1 or 2, having a tensile strength of 690 MPa or more measured at 25°C.

4. The austenitic stainless steel according to claim 1 or 2, wherein the grain size number of the austenite grains of the austenitic stainless steel is less than 8.

0.

5. The austenitic stainless steel according to claim 1 or 2, wherein the austenitic stainless steel has a cross-sectional reduction rate of 30% or more measured at 25°C.

6. A hydrogen resistant component comprising the austenitic stainless steel according to claim 1 or 2.

7. The hydrogen resistant component according to claim 6, wherein: The austenitic stainless steel includes a portion in a solution treated state.

8. The hydrogen resistant member according to claim 6, comprising a butt-welded portion, wherein: The welding tensile strength of the butt welded portion measured at 25° C. is 690 MPa or more.

Citation Information

Patent Citations

  • Service providing device, application program, service providing system, service providing method and program

    JP2023165246A

  • Composition and heat storage material

    JP2024118404A

  • Austenitic stainless steel material

    WO2017175739A1

Cited By

  • Corrosion-resistant high-nitrogen low-nickel stainless steel and preparation method thereof

    CN121228130A